Researching the application of virtual reality in medical education: one-year follow-up of a randomized trial - Wenyi Gan; Tsz-Ngai Mok; Junyuan Chen; Guorong She; Zhengang Zha; Huajun Wang; Hua Li; Jieruo Li; Xiaofei Zheng (BMC Medical Education, 2023)
Abstract Background Compared with traditional tendon repair teaching methods, using a virtual reality (VR) simulator to teach tendon suturing can significantly improve medical students’ exercise time, operation flow and operation knowledge. At present, the purpose of this study is to explore the long-term influence of VR simulator teaching on the practice performance of medical students. Method This is a one-year long-term follow-up study of a randomized controlled study. A total of 117 participants who completed the initial study were invited to participate in the follow-up study. Participants in the VR group and the control group were required to complete a questionnaire developed by the authors and the teachers in the teaching and research department and to provide their surgical internship scores and Objective Structure Clinical Examination(OSCE) graduation scores. Results Of the 117 invitees, 108 completed the follow-up. The answers to the questions about career choice and study habits were more positive in the VR group than in the control group (p < 0.05). The total score for clinical practice in the VR group was better than that in the control group, and the difference was statistically significant (p < 0.05). In the OSCE examination, the scores for physical examination, suturing and knotting and image reading were higher in the VR group than in the control group, and the difference was statistically significant (p < 0.05). Conclusion The results of the one-year long-term follow-up indicated that compared with medical students experiencing the traditional teaching mode, those experiencing the VR teaching mode had more determined career pursuit and active willingness to learn, better evaluations from teachers in the process of surgical clinical practice, and better scores in physical examination, suturing and knotting and image reading in the OSCE examination. In the study of nonlinear dynamics to cultivate a good learning model for medical students, the VR teaching model is expected to become an effective and stable initial sensitive element. Trial registration Chinese Clinical Trial Registry(25/05/2021, ChiCTR2100046648); http://www.chictr.org.cn/hvshowproject.aspx?id=90180 .